2006
DOI: 10.1007/s00299-006-0148-z
|View full text |Cite
|
Sign up to set email alerts
|

Refining the application of direct embryogenesis in sugarcane: effect of the developmental phase of leaf disc explants and the timing of DNA transfer on transformation efficiency

Abstract: A rapid in vitro protocol using direct somatic embryogenesis and microprojectile bombardment was investigated to establish the developmental phases most suitable for efficient sugarcane transformation. Immature leaf roll disc explants with and without pre-emergent inflorescence tissue were compared. It was shown that for effective transformation to occur, explants should be cultured for several days to allow initiation of embryo development prior to bombardment. Leaf roll discs with pre-emergent inflorescences… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
49
0
13

Year Published

2008
2008
2020
2020

Publication Types

Select...
4
3
3

Relationship

0
10

Authors

Journals

citations
Cited by 69 publications
(64 citation statements)
references
References 39 publications
2
49
0
13
Order By: Relevance
“…For this study, 4 sugarcane varieties were selected, namely cultivars CPF-234, CPF-213, HSF-240, and CPF-246, and their young immature leaves were used as explants to induce calli. Snyman et al (2006) also suggested that immature leaves of sugarcane prove to be an excellent explant for production of an embryogenic, friable callus. Optimization for friable, embryogenic calli is not only mandatory for genetic manipulation of sugarcane but also strengthens the development of the transformation system in sugarcane (Fitch et al, 2001).…”
Section: Discussionmentioning
confidence: 99%
“…For this study, 4 sugarcane varieties were selected, namely cultivars CPF-234, CPF-213, HSF-240, and CPF-246, and their young immature leaves were used as explants to induce calli. Snyman et al (2006) also suggested that immature leaves of sugarcane prove to be an excellent explant for production of an embryogenic, friable callus. Optimization for friable, embryogenic calli is not only mandatory for genetic manipulation of sugarcane but also strengthens the development of the transformation system in sugarcane (Fitch et al, 2001).…”
Section: Discussionmentioning
confidence: 99%
“…Sob ausência de auxina no meio de regeneração, os brotos regenerados provenientes de embriões somáticos foram produzidos neste experimento, assim como os trabalhos de Falco et al (2000) e Snyman et al (2006). Visando obter plantas bem desenvolvidas, os brotos regenerados foram subcultivados novamente em meio de regeneração por 21 dias.…”
Section: Methodsunclassified
“…It has now become a valuable alternative to the conventional clonal propagation methods for seed production. Tissue culture can increase the propagation potential by 20-35 times (Geijskes et al, 2003, Snyman et al, 2006. In addition, plants can be disease-indexed (Snyman et al, 2007) and healthy material multiplied in much less time compared to the conventional vegetative route.…”
Section: Introductionmentioning
confidence: 99%